2021
DOI: 10.21203/rs.3.rs-279516/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Effect of anticholinergic burden on the onset of delirium in elderly hospitalized patientsassessed by 3 anticholinergic scales

Abstract: Background: Several studies have demonstrated the deleterious effects of anticholinergic drugs on the cognitive functions of the elderly. However, their effects on the onset of delirium have produced conflicting results. We assessed the association of the anticholinergic burden of treatment at admission according to 3 anticholinergic scales, the ADS, the modified ADS (mADS) and the Marante Scale on the onset of delirium in elderly hospitalized patients. We also analyzed the inter-rater reliability of the scale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 32 publications
0
0
0
Order By: Relevance
“…Other studies have shown similar results. Using the Belgian scale, studies carried out in Belgium revealed that 31.80 to 45.00% of the studied populations were exposed to drugs with anticholinergic activity, 12,19,20 compared to 58.45% according to the Brazilian scale in a study with patients from an inpatient unit carried out in Switzerland. 21 Although the Belgian scale may provide more accurate anticholinergic burden estimation by combining anticholinergic dosage and potency, the analysis is limited to only 41 active substances out of the 100 anticholinergics available internationally.…”
Section: Discussionmentioning
confidence: 98%
“…Other studies have shown similar results. Using the Belgian scale, studies carried out in Belgium revealed that 31.80 to 45.00% of the studied populations were exposed to drugs with anticholinergic activity, 12,19,20 compared to 58.45% according to the Brazilian scale in a study with patients from an inpatient unit carried out in Switzerland. 21 Although the Belgian scale may provide more accurate anticholinergic burden estimation by combining anticholinergic dosage and potency, the analysis is limited to only 41 active substances out of the 100 anticholinergics available internationally.…”
Section: Discussionmentioning
confidence: 98%